Low-Temperature Synthesis and Structural Properties of PbMoO4 Nanocrystals - Atuchin, V.V.; Andreeva, O.P.; Korolkov, I.V.; Maximovskiy, E.A.; Lim, C.S. (Asian Journal of Chemistry, 2014)
Lead molybdate (PbMoO4) nanocrystals have been synthesized by coprecipitation method in aqueous solution. The phase composition and micromorphology of the reaction product have been evaluated by XRD and SEM analysis. The characteristic diameter of PbMoO4 nanocrystals has been estimated as 100 nm.